INVESTIGATING THE COURSES OF IMPLEMENTATION BY DESCRIBING RESARCH PERFOMANCE - KAYA, Akiko; OKUWADA, Kumi (SOCIOTECHNICA, 2015)
Nowadays, despite the fact that researchers are wanted to create performance that solve the problems of society and the word "implementation" is beginning to spread among people, the definition of the word itself cannot derive a uniform expertise. This paper makes an attempt to describe performance of research and development that are recommended to be implemented. In consequence, it becomes clear that four out of ten projects attain the phase of implementation. Concept of implementation must be more widespread than initially envisioned. In addition, this paper also examines the correlation of novelty in implementation and research technique together with that of general versatility in implementation and performance.